Design of metal-organic frameworks for improving pseudo-solid-state magnesium-ion electrolytes: Open metal sites, isoreticular expansion, and framework topology. (1st May 2023) - Zheng, Yun; Guo, Junpo; Ning, De; Huang, Yike; Lei, Wen; Li, Jing; Li, Jianding; Schuck, Götz; Shen, Jingjun; Guo, Yan; Zhang, Qi; Tian, Hao; et al.
Highlights: Systematic research for constructing magnesium-ion solid-state electrolytes based on reticular chemistry. Molecular insights into boosting ionic conductivity based on open metal sites. Optimizing of framework topology for improving Mg 2+ transport dynamics. Abstract: The design criteria for metal-organic frameworks (MOFs) have been established by evaluating the relationship between their key characteristics and magnesium-ion conductivity based on three types of secondary building blocks (Zn4 O(CO2 )6 :MOF-5 and MOF-177; Cu2 (CO2 )4 :MOF-199, MOF-143, MOF-14, and MOF-399; Cu2 O2 (CO2 )2 :Cu-MOF-74) to achieve pseudo-solid-state magnesium-ion conduction. We found that open-metal sites and channel layouts play a pivotal role in promoting magnesium-ion transport dynamics at reduced activation energy, transforming MOF scaffolds into ionic-channel analogs. X-ray absorption spectroscopy combined with Raman and Fourier-transform infrared spectroscopy predicted the chemical environment, solvents, and anions that occupied coordinatively unsaturated metal sites. The chemical compositions of electrolytes determined by 1 H-NMR (nuclear magnetic resonance) and organic elemental analysis confirmed that isoreticular expansion increases the molar percentage of charge carriers, providing high conductivity. The current research systematically reveals the impacts of different MOF characteristics on ionic conduction performance, paving the way for the construction of a new class of fast and selective multivalent-ion pseudo-solid electrolytes.